Inclusive didactic and entry competence of teachers enrolled in the Support Specialization Course. Results of an exploratory survey - Valentina Pennazio; Franco Bochicchio (Firenze University Press, 2021)
The paper presents the results of a survey carried out with the teachers of the four school orders enrolled in the 2019-2020 academic year in the fifth cycle of the TFA Support Course organized by the Department of Education of the University of Genoa. The purpose of the survey was to detect information: (1) on the students' input knowledge about the skills that outline the profile of the specialized teacher for support activities and (2) on their perception of proximity to the skills investigated. The results obtained were compared with those of a survey of the same type conducted in the years 2013/2014. This made it possible to draw initial observations on the evolution of the idea of inclusive teaching with which teachers currently approach the specialization course for support activities.   Didattica inclusiva e competenze di ingresso degli insegnanti iscritti al Corso di specializzazione per il sostegno. Esiti di un'indagine esplorativa Il contributo presenta gli esiti di un'indagine realizzata con gli insegnanti dei quattro ordini di scuola iscritti nell'anno accademico 2019-2020 al V ciclo del Corso TFA sostegno organizzato dal Dipartimento di Scienze della Formazione dell'Università di Genova. Lo scopo dell'indagine è stato quello di rilevare informazioni: (1) sulle conoscenze in ingresso dei corsisti circa le competenze che delineano il profilo dell'insegnante specializzato per le attività di sostegno e (2) sulla loro percezione di vicinanza alle competenze indagate. I risultati ottenuti sono stati comparati con quelli di un'indagine dello stesso tipo condotta negli anni 2013/2014. Questo ha consentito di trarre prime osservazioni sull'evoluzione dell'idea di didattica inclusiva con cui i docenti approcciano attualmente il corso di specializzazione per le attività di sostegno.